2017
DOI: 10.1002/ceat.201600561
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Waste Cooking Oil Transesterification with Microwave Heating and Strontium Oxide Catalyst

Abstract: Biodiesel produced from waste cooking oils (WCOs) mixed with methanol was efficiently transesterified using a continuous fluid flow system with a focused microwave heating device. Strontium oxide (SrO) was added as the catalyst. The factors that most influence the biodiesel conversion rate were first estimated by considering the effects of oil-to-methanol ratio, added quantity of SrO, and microwave heating power on reaction time in a built-in batch unit. The optimal parameter values were then applied to a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The alcohol is deprotonated with a base to make nucleophile tougher in the transesterification procedure [39]. Despite natural variations (e.g., those caused by the degradation of the SrO catalyst and the quality of olive oil), the conversion process of olive oil into biodiesel and the reaction rate are mainly based on the formation of the transesterification reaction [12]. SrO catalyst lowers the activation energy for the transesterification reaction, which promotes the decomposition of ester bonds and the formation of a tetrahedral intermediate substance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The alcohol is deprotonated with a base to make nucleophile tougher in the transesterification procedure [39]. Despite natural variations (e.g., those caused by the degradation of the SrO catalyst and the quality of olive oil), the conversion process of olive oil into biodiesel and the reaction rate are mainly based on the formation of the transesterification reaction [12]. SrO catalyst lowers the activation energy for the transesterification reaction, which promotes the decomposition of ester bonds and the formation of a tetrahedral intermediate substance.…”
Section: Resultsmentioning
confidence: 99%
“…Factors that may affect the reaction include the reaction temperature and the evaporation of methanol, which will also be varied with the oil:methanol ratio [40,41,42]. Previous studies have shown that the optimal oil-to-methanol ratio is about 1:6 [12]. Other ratios such as 1:4 and 1:8 have been studied.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations